Fast Optical Beamforming Architectures for Satellite-Based Applications. (15th October 2012) - Vidal, B.; Mengual, T.; Martí, J.
Abstract : Photonic technology offers an alternative implementation for the control of phased array antennas providing large time bandwidth products and low weight, flexible feeding networks. Measurements of an optical beamforming network for phased array antennas with fast beam steering operation for space scenarios are presented. Experimental results demonstrate fast beam steering between 4 and 8 GHz without beam squint.